Derby girl - Cross, Shauna (Henry Holt and Company, 2007)
When sixteen-year-old rebel Bliss Cavendar, who is miserable living in a small Texas town with her beauty pageant-obsessed mother, secretly joins a roller derby team under the name "Babe Ruthless," her life gets better, although infinitely more confusing.